Novel uses of healthcare technology for individuals with mild to moderate hip or knee osteoarthritis: The technology, exercise and activity prescription for enhanced mobility (TEAM) study randomized controlled trial protocol - Jane Thornton; Kristen I. Barton; Laura Churchill; Jenna M. Schulz; Dianne Bryant; Ashley Ambrose; Harvi F. Hart; Daryl Stephenson; Guangyong Zou; Susana Correa; Steven J. MacDonald; Ryan Degen; et al. (Osteoarthritis and Cartilage Open)
Objectives: Patient education, physical activity, and exercise are recommended as first-line treatments for mild to moderate hip and knee osteoarthritis (OA). We developed two novel healthcare interventions: an electronic medical record-embedded physical activity prescription tool (PARx) for physicians, and a free, online educational platform (Joint Management (JM)) with exercise programming and optional telerehabilitation with a physiotherapist for patients. Objectives: 1) Determine the effectiveness of PARx ​± ​JM on patient-reported outcomes, physical activity levels, and performance-based functional outcomes in individuals with mild to moderate hip or knee OA, versus usual care; 2) evaluate engagement and adherence to PARx ​+ ​JM; and 3) explore the feasibility of PARx and PARx ​+ ​JM. Registration: NCT04544904. Methods: Randomized controlled trial (type 1 hybrid implementation effectiveness). We will recruit 339 (113/group) participants ≥40 years old with mild to moderate hip or knee OA and randomize them into three groups: PARx, PARx ​+ ​JM, or control (usual care). Follow-up appointments will be completed at 2-, 6-, and 12-months. Primary outcome: Knee Injury/Hip Disability and OA Outcome Score. Secondary outcomes: physical activity levels, anthropometric measurements, physical function, and other patient-reported outcomes. We will assess intervention feasibility and hold focus groups with patients and providers to explore perceptions of the interventions. Conclusion: Two novel healthcare interventions will be used to provide physical activity and exercise programming for individuals with mild-moderate knee and hip OA. This study will allow us to determine the effectiveness of these interventions on patient-reported outcomes, physical activity levels, and performance-based functional outcomes.